2009
DOI: 10.1002/jsfa.3852
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the quality and abatement of the biogenic amines of grass carp muscles by fermentation using mixed cultures

Abstract: Fermentation with mixed starter cultures of L. casei, S. lactis, S. cerevisiae Hansen and M. anka significantly improved the characteristics of grass carp muscles and controlled the accumulation of biogenic amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Among them, putrescine had the highest content (3.0 mg/kg DW), followed by tyramine (2.6 mg/kg DW), spermine (2.0 mg/kg DW), spermidine (1.4 mg/kg DW), and cadaverine (1.1 mg/kg DW), but no histamine was detected. The results were similar to those of Liu et al (2010), except that small amount of histamine (0.28 mg/kg) but no cadaverine was detected in their samples. The slight differences may be due to the different fish culture locations of the grass carp (Zhejiang Province vs Hunan Province).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Among them, putrescine had the highest content (3.0 mg/kg DW), followed by tyramine (2.6 mg/kg DW), spermine (2.0 mg/kg DW), spermidine (1.4 mg/kg DW), and cadaverine (1.1 mg/kg DW), but no histamine was detected. The results were similar to those of Liu et al (2010), except that small amount of histamine (0.28 mg/kg) but no cadaverine was detected in their samples. The slight differences may be due to the different fish culture locations of the grass carp (Zhejiang Province vs Hunan Province).…”
Section: Resultssupporting
confidence: 82%
“…It is popular not only for its special chewiness and flavor but also longer shelf life (Tan et al 2006). In terms of nutrition, cured fish is a rich source of high quality proteins as well as some vitamins and minerals (Liu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The initial values of TRM, PUT, HIM, SPD, and SPM were 1.77, 0.53, 28.62, 1.16, and 6.31 mg/kg, respectively. SPD and SPM are considered natural amines in fish muscle (8,17). The initial concentrations of SPD and SPM were similar to the research on grass carp reported by Zhai et al (32).…”
Section: Resultssupporting
confidence: 81%
“…research has focused on the control of BA formation, such as high pressure treatments (19), modified atmosphere packaging (4), and fermentation (17). However, few reports have focused on the formation of BAs as influenced by salt concentration.…”
mentioning
confidence: 99%
“…Monascus species can esterify mixed acids and ethanol to form esters such as ethyl caproate that contribute to the aroma of the Chinese liquor. This species can also produce citric acid, acetic acid, succinic acid, and substances with physiological activity that facilitate the formation of flavor and provide health benefits [14,16].…”
Section: Molds Are Dominant In the Fungal Communitymentioning
confidence: 99%